Verbal Humor in American Situational Comedy the Office: Semantics View - Rahayu Pujianti, Tika; Nehe, Berita Mambarasi Nehe; Siswanto, Puji (English Education, Linguistics, and Literature Journal, 2024)
The semantic analysis attempts to define and completely comprehend the word’s meaning. The purpose of this study was to delve into the types of lexical relations in verbal humor and investigate the humor styles of the American sitcom The Office. This study used a qualitative design to collect data on verbal humor. The findings revealed that The Office frequently uses homonym, polysemy, hyponym, antonym and synonym in the construction of humor and potentially creates a humorous effect. Additionally, the humor style of the sitcom is sarcastic humor. It can be concluded that linguistically the use of homonym, polysemy, hyponym, antonym and synonym in the punchline provides an amusing effect and generates a comical situation. On the other hand, it also creates an ambiguity effect which results in a double interpretation of certain jokes due to the multiple meanings of a single word.